Vozes castelhanas na tradição portuguesa (textos metagramaticais e metaortográficos) - Duarte, Sónia (Revista da Associação Portuguesa de Linguística, 2016)
This paper briefly depicts the presence of Spanish authors on Portuguese grammars and orthographies up to the 19th century, by exposing and analysing the most significant data conveyed by the texts. Bearing in mind the theoretical framework known as the language issue in Portugal, this essay attempts to determine which Spanish bibliographical sources were known to the Portuguese tradition and interpret their meaning concerning the level of familiarity with the Spanish tradition, as well as the point of view of Portuguese authors on those same sources.